Increased non‐AIDS mortality among persons with AIDS‐defining events after antiretroviral therapy initiation. Issue 1 (15th January 2018) - Pettit, April C; Giganti, Mark J; Ingle, Suzanne M; May, Margaret T; Shepherd, Bryan E; Gill, Michael J; Fätkenheuer, Gerd; Abgrall, Sophie; Saag, Michael S; Del Amo, Julia; Justice, Amy C; Miro, Jose M; et al.
Abstract: Introduction: HIV‐1 infection leads to chronic inflammation and to an increased risk of non‐AIDS mortality. Our objective was to determine whether AIDS‐defining events (ADEs) were associated with increased overall and cause‐specific non‐AIDS related mortality after antiretroviral therapy (ART) initiation. Methods: We included HIV treatment‐naïve adults from the Antiretroviral Therapy Cohort Collaboration (ART‐CC) who initiated ART from 1996 to 2014. Causes of death were assigned using the Coding Causes of Death in HIV (CoDe) protocol. The adjusted hazard ratio (aHR) for overall and cause‐specific non‐AIDS mortality among those with an ADE (all ADEs, tuberculosis (TB), Pneumocystis jiroveci pneumonia (PJP), and non‐Hodgkin's lymphoma (NHL)) compared to those without an ADE was estimated using a marginal structural model. Results: The adjusted hazard of overall non‐AIDS mortality was higher among those with any ADE compared to those without any ADE (aHR 2.21, 95% confidence interval (CI) 2.00 to 2.43). The adjusted hazard of each of the cause‐specific non‐AIDS related deaths were higher among those with any ADE compared to those without, except metabolic deaths (malignancy aHR 2.59 (95% CI 2.13 to 3.14), accident/suicide/overdose aHR 1.37 (95% CI 1.05 to 1.79), cardiovascular aHR 1.95 (95% CI 1.54 to 2.48), infection aHR (95% CI 1.68 to 2.81), hepatic aHR 2.09 (95% CI 1.61 to 2.72), respiratory aHR 4.28 (95% CI 2.67 to 6.88), renal aHR 5.81 (95% CI 2.69 to 12.56) and central nervous aHR 1.53 (95% CI 1.18 to 5.44)). The risk of overall and cause‐specific non‐AIDS mortality differed depending on the specific ADE of interest (TB, PJP, NHL). Conclusions: In this large multi‐centre cohort collaboration with standardized assignment of causes of death, non‐AIDS mortality was twice as high among patients with an ADE compared to without an ADE. However, non‐AIDS related mortality after an ADE depended on the ADE of interest. Although there may be unmeasured confounders, these findings suggest that a common pathway may be independently driving both ADEs and NADE mortality. While prevention of ADEs may reduce subsequent death due to NADEs following ART initiation, modification of risk factors for NADE mortality remains important after ADE survival.